Characterizing the protein composition of the CIA Targeting Complex (CTC) in Toxoplasma gondii parasites. - Evie R. Hodgson (21866946) (2025)
(A) Western blot of proteins extracted from rTgDre2-mAID-HA, rTgTah18-mAID-HA, and rHA-mAID-TgNar1/TgCIA1-smFP-cMyc parasites, separated by BN-PAGE and probed with anti-HA antibodies to detect the TgDre2-mAID-HA, TgTah18-mAID-HA, and HA-mAID-TgNar1 proteins. (B, C) Western blots of proteins extracted from rTgCIA1-mAID-cMyc/TgCIA2-HA parasites cultured for 0–12 h in IAA, separated by (B) SDS-PAGE or (C) BN-PAGE and probed with anti-HA antibodies to detect the TgCIA2-HA protein, anti-cMyc antibodies to detect the TgCIA1-mAID-cMyc protein, and anti-TgTom40 antibodies as a loading control. For the SDS-PAGE western blots (B), the relative abundance of the TgCIA2-HA protein was determined as a percentage of the 0 h IAA control, with abundances normalized using the TgTom40 loading control. Data points represent the mean ± SD of three independent experiments. Data were analyzed using a one-way ANOVA followed by Tukey’s multiple comparisons test with relevant p values shown. The numerical data underlying this Figure can be found in S1 Data. In the BN-PAGE western blot (C), the black arrowhead indicates the >720 kDa candidate CIA Targeting Complex. (D) Western blot of proteins extracted from rTgCIA2-mAID-HA/TgCIA1-smFP-cMyc parasites and immunoprecipitated using anti-HA- or anti-cMyc-conjugated agarose beads. Extracted fractions include total protein prior to immunoprecipitation (T), unbound proteins (U), and antibody-bound proteins (B) in the indicated proportions. Protein fractions were separated by SDS-PAGE and probed with anti-cMyc, anti-HA, or anti-TgTom40 antibodies. Data are representative of three independent experiments for the anti-HA immunoprecipitation and two independent experiments for the anti-cMyc immunoprecipitation. Asterisks depict likely degradation products of the TgCIA1-smFP-cMyc protein. (TIF)